A Nonlinear Backstepping Controller for Inverters used in Microgrids. Issue 1 (July 2017) - Ammeh, L.; Fadil, H. El; Yahya, A.; Ouhaddach, K.; Giri, F.; Ahmed-Ali, T.
Abstract: This paper proposes a nonlinear controller for Voltage Source Inverter (VSI) used in microgrids. The controlled system includes the VSI, an LC filter, a coupling inductor, and loads. The controller is designedon the basis of the averaged system model, using the backstepping technique and the droop control method. The controller stability is theoretically analyzed and its performances are illustrated by simulation in different grid operation modes(connected and islanded)and load changes.